2021
DOI: 10.3390/ani11041007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postbiotic Based on Lactic Acid Bacteria on Semen Quality and Health of Male Rabbits

Abstract: The aim of this study was to evaluate the effect of lactic acid bacteria-based postbiotic supplementation on semen characteristics and hematological and biochemical profiles in rabbits. A total of 28 males were randomly allocated into two groups. Males received a Control diet and Enriched diet supplemented with postbiotic for 15 weeks (4 weeks of adaptation period and 11 weeks of experimental period). Body weight, feed intake and semen characteristics were recorded weekly. Hematological profile was recorded at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the positive regulatory impact of oral probiotic consumption on sperm quality via the modulation of the reproductive hormone levels or anti-inflammatory response in male animal models [ 64 , 65 ] and humans [ 66 , 67 ]. Concerning postbiotics, a study by Díaz et al [ 68 ] examined the impact of oral postbiotics on sperm motility. This study, conducted on rabbits, revealed that 11 weeks of oral supplementation with postbiotics based on lactic acid bacteria led to fewer abnormal spermatozoa and increased acrosome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the positive regulatory impact of oral probiotic consumption on sperm quality via the modulation of the reproductive hormone levels or anti-inflammatory response in male animal models [ 64 , 65 ] and humans [ 66 , 67 ]. Concerning postbiotics, a study by Díaz et al [ 68 ] examined the impact of oral postbiotics on sperm motility. This study, conducted on rabbits, revealed that 11 weeks of oral supplementation with postbiotics based on lactic acid bacteria led to fewer abnormal spermatozoa and increased acrosome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Humam et al [54] reported that the supplementation of postbiotics to broilers raised under stress conditions led to higher counts of beneficial microorganisms in the caecum and a significantly lower population of pathogenic bacteria, such as Escherichia coli and Salmonella, compared to the control groups. In the field of assisted reproduction in intensive livestock farming, a recent study evaluating the seminal quality of rabbits has shown that a significant improvement in semen characteristics and liver profile resulted from the administration of a postbiotic derived from lactic acid bacteria [163].…”
Section: Benefits As Postbioticsmentioning
confidence: 99%
“…When evaluating a new feed additive for domestic animals, it is essential to analyze the effects of the consumption of the additive on animal health [31]. According to Diaz Cano et al [61], knowledge of reference values for blood metabolites in rabbits provides valuable information on the health status of the animals. In particular, hematological parameters provide information on rabbits' visceral organ infections, inflammation, and necrosis [62].…”
Section: Hematological Parameters and Blood Biochemistrymentioning
confidence: 99%
“…If analyzed at appropriate reference intervals, serum uric acid and creatinine concentrations can be used as biomarkers of renal function status in rabbits [61]. For example, serum creatinine levels increase above the reference interval when animals have chronic and acute renal failure [69].…”
Section: Hematological Parameters and Blood Biochemistrymentioning
confidence: 99%